Human umbilical cord mesenchymal stem cells-derived exosomal microRNA-451a represses epithelial–mesenchymal transition of hepatocellular carcinoma cells by inhibiting ADAM10. Issue 10 (3rd October 2021) - Xu, Yunxiuxiu; Lai, Yu; Cao, Linhui; Li, Yanshan; Chen, Guangcheng; Chen, Liang; Weng, Hanqin; Chen, Tao; Wang, Lingyun; Ye, Yibiao
ABSTRACT: Exosomes derived from human umbilical cord mesenchymal stem cells (hucMSCs) expressing microRNAs (miRNAs) have been highlighted in human cancers. However, the detailed molecular mechanism of hucMSCs-derived exosomal miR-451a on hepatocellular carcinoma (HCC) remains further investigation. Our study aims to explore the impact of exosomal miR-451a on the progression of HCC. Expression of miR-451a and a disintegrin and metalloprotease 10 (ADAM10) in HCC tissues and adjacent normal tissues were determined. The exosomes were extracted from hucMSCs and co-cultured with Hep3B and SMMC-7721 cell lines. After the treatment of relative exosomes or exosome inhibitor GW4869 in Hep3B and SMMC-7721 cells, the paclitaxel resistance and malignant phenotypes of HCC cells were measured. Moreover, the effect of hucMSCs-derived exosomes on the expression of miR-451a and ADAM10 in HCC cells was assessed. The targeting relationship between miR-451a and ADAM10 was verified to detect the impact of ADAM10-wild type and ADAM10-mutant type (MUT) on HCC cell processes. Low expression of miR-451a and high expression of ADAM10 indicated a poor prognosis of HCC patients. MiR-451a was up-regulated while ADAM10 was down-regulated in HCC cells after co-culture with HucMSC-derived exosomes. The exosomes elevated miR-451a and inhibited ADAM10 to suppress the paclitaxel resistance, cell cycle transition, proliferation, migration and invasion, and promote apoptosis of HCC cells. ADAM10 was verified to be a target gene of miR-451a. ADAM10-MUT promoted HCC process independent of miR-451a mimic. HucMSC-derived exosomal miR-451a could restrict the epithelial–mesenchymal transition of HCC cells by targeting ADAM10, which might provide new targets for HCC treatment.